2020
DOI: 10.1111/jdi.13193
|View full text |Cite
|
Sign up to set email alerts
|

Decreased microcirculatory function measured by perfusion index is a novel indicator of diabetic kidney disease in patients with type 2 diabetes

Abstract: Aims/Introduction: Diabetic kidney disease has been considered as an important risk factor of cardiovascular disease. Chronic hypoxia is considered to be the main cause of renal injury. Diminished microcirculatory blood flow could be associated with hypoxia in the kidney. Whether diminished microcirculation is associated with diabetic kidney disease has not yet been reported. Here, we investigated the correlation between microcirculatory function and diabetic kidney disease in patients with type 2 diabetes. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…High systolic blood pressure or low perfusion index had markedly increased odds of ACR and eGFR. 15 Clinically, TcPO2 was also frequently used as a useful tool to assess microcirculation in diabetic patients. Previous study indicated optimal cutoff point (19.5 mm Hg) yielded a sensitivity of 0.611 and a specificity of 0.738 for predicting DPN.…”
Section: Discussionmentioning
confidence: 99%
“…High systolic blood pressure or low perfusion index had markedly increased odds of ACR and eGFR. 15 Clinically, TcPO2 was also frequently used as a useful tool to assess microcirculation in diabetic patients. Previous study indicated optimal cutoff point (19.5 mm Hg) yielded a sensitivity of 0.611 and a specificity of 0.738 for predicting DPN.…”
Section: Discussionmentioning
confidence: 99%
“…5 Transcutaneous oxygen pressure (TcPO2) is the oxygen content of capillaries that diffuse through the skin, It can be used for the evaluation of skin blood flow perfusion volume and microcirculation function. 6 Muscle oxygen Saturation (SmO2) reflects muscle oxygen supply balance and muscle generation Xie's important indicator has a close relationship to TcPO2. 7 Based on this, In this study, aerobic exercise and aerobic were formulated to FATmax as exercise intensity standard In combination with the resistance exercise protocol, 10 weeks of aerobic exercise and aerobic binding resistance were explored Shadow of exercise on microvascular reactivity, TcPO2 and SmO2 in obese college students Ring, and explore the possible mechanism of exercise to improve the microcirculation function, to improve fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, renal injury is often caused by I/R treatment in diabetes. 11,12 However, studies on the renal I/R injury in diabetes are still inadequate nowadays.…”
Section: Introductionmentioning
confidence: 99%